An Anionic Microporous Polymer Network Prepared by the Polymerization of Weakly Coordinating Anions1. Issue 46 (22nd October 2013) - Fischer, Sabrina; Schmidt, Johannes; Strauch, Peter; Thomas, Arne
<x xml:space="preserve">Abstract</x> Organic zeolite: A microporous, covalent organic network with high surface area was synthesized by polymerization of [B(C6F4Br)4]−. The countercations, located within the pore channels, are highly accessible and can be easily exchanged, comparable to the extra‐framework cations in zeolites. In this way a [MnII(bpy)]2+ complex can be synthesized and immobilized in the network.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>